(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
E-government is the delivery of government services and information of public importance through electronic means, whereas e-government support refers to the actual carrying out of this duty by the government. In other words, e-governance refers to the use of more minimal electronic systems in government operations, with the goal of storing, gathering, recognizing, and disseminating bandwidth and data affecting daily operations to the civilian population on demand. The term "e-governance" refers to the use of the Internet and related technologies to improve the efficiency, effectiveness, accountability, and openness of government. In this paper research e-governance service in haryana municipal corporation.